PENGARUH IKLAN ONLINE INSTAGRAM, SISTEM PEMBAYARAN DAN PERSEPSI HARGA TERHADAP LOYALITAS PELANGGAN MICKEY DIMSUM TEBING TINGGI - Fayza; Dinda Ameilia Putri; Sinurat, Yenni Mariani; Nursaimatussaddiya (JURNAL ILMIAH EDUNOMIKA, 2025)
Maintaining customers is important for the sustainability of every company's business. The high level of competitors can cause an increase in customer loyalty. The purpose of this study is to determine whether Online Advertising, Payment Systems, and Price Perceptions affect Mickey Dimsum Customer Loyalty. The method used is a quantitative research method. The sampling used in this study is the Non Probability sampling method and the type of sampling using Accidental sampling, the number of samples studied was 96 respondents. This study uses the help of SPSS 25 Software. Data analysis techniques in this study are Instrument Testing, Classical Assumption Testing, Multiple Linear Regression Analysis, Determinant Coefficient Testing, Hypothesis Testing. The research that has been conducted has concluded that Online Advertising does not affect Customer Loyalty. Payment Systems do not affect Customer Loyalty. Price Perception has a Positive and significant effect on Customer Loyalty. Online Advertising, Payment Systems, and Price Perception have a simultaneous effect on Customer Loyalty. Keywords: Instagram Online Advertising, Payment Systems, Price Perception, Customer Loyalty